The role of genetic diversity, epigenetic regulation, and sex-based differences in HIV cure research: a comprehensive review - Punitha Letchumanan; Kumitaa Theva Das (Epigenetics & Chromatin)
Abstract Despite significant advances in HIV treatment, a definitive cure remains elusive. The first-in-human clinical trial of Excision BioTherapeutics’ CRISPR-based HIV cure, EBT-101, demonstrated safety but failed to prevent viral rebound. These outcomes may result from the interplay of several factors. Growing evidence indicates that intricate epigenetic modifications play a major role in the persistence of HIV latency, presenting a significant barrier to eradication efforts and causing viral rebound after ART discontinuation. Current strategies to purge the latent reservoir involve LRAs that reactivate latent proviruses. However, their clinical success is hindered by the heterogeneity of HIV reservoirs and the virus’s diverse pathways. Additionally, RNA modifications like N6-methyladenosine (m^6 A) methylation influence HIV biology beyond transcriptional control, affect RNA stability, splicing, and translation, which could enhance therapeutic efficacy. The regulatory framework of chromatin dynamics is also key to understanding viral latency and reactivation, such as Vpr’s role in reactivating latent HIV by targeting HDACs. Sex-specific factors were also shown to play an important role with females, showing stronger early immune responses and higher representation among elite controllers. This review addresses the multifaceted challenges of HIV cure research, focusing on genetic diversity, epigenetic regulation, RNA modifications, chromatin remodeling, and sex-specific factors. By integrating insights into these aspects, this paper aims to advance our understanding of HIV cure strategies and highlight directions for future research.